Вдосконалення технології гарячого ремонту футерівки конвертера з використанням розробленої магнезіальної маси марки «GIR-RB-X» - Немсадзе, Г.Г.; Смірнов, О.М.; Джоджуа, Р.А.; Шарандін, К.М.; Рябий, Д.М. (Physico-technological Institute of Metals and Alloys, 2023)
The analysis of methods of hot repair of areas of advanced wear of working, periclase-carbon lining of converters by a method of welding is carried out. The technique of estimation of quality of self-flowing, magnesian, welding mass on laboratory furnace of rotor type, which has no analogues in Ukraine is developed. The developed technique allows reaching high level of reliability of the received results that allows transferring the received experience on industrial conditions, at rather low power inputs and high safety in comparison with carrying out of experiments in the real metallurgical unit. According to the results of laboratory researches the repair, self-flowing, cellar mass of “GIR-RB-X” brand is developed, on the basis of secondary, domestic raw materials, allowing to restore effectively the areas of refractory lining of the converter, which are subject to advanced wear and tear, to prolong its working campaign and thereby to reduce specific costs for steel production. Industrial tests of self-flowing, magnesium and repair masses were carried out on heavy-duty converter linings at metallurgical enterprises of PJSC “DMK” and PJSC “Azovstal Iron and Steel Works”. The results of the tests testify to the high competitiveness of the developed mass in comparison with foreign analogues, as well as the flexibility of the developed welding mass to different operating conditions of the converter. GIR-Engineering LLC organized serial production of self-flowing repair mass of “GIR-RB-X” brand at the production facilities of PJSC “KrOZ” with the use of high-tech line of “Eirich” company and automatics of “Siemens” company, which allows to achieve high quality of finished products.